PENERAPAN DATA MINING DENGAN METODE INTERPOLASI UNTUK ESTIMASI PREMI BERDASARKAN PENDAPATAN NASABAH ASURANSI PRUDENTIAL DI YOGYAKARTA - Pandapotan Pandapotan; Anton Setiawan Honggowibowo; Dwi Nugraheny (Compiler, 2012)
Premi in a definition can be interpreted as a fee to be paid by the customer, which is a combination of the overall cost of insurance benefits that used, and sometimes also include the amount of money invested by customers. The output of the data mining is a customers is accepted according to the prudential value of the estimated premi be gained from the number of customer revenue.Final project is, created a program of web-based application system to estimate the premi to make it easier for admin (prudential employee)  to determine the amount of premi to be paid by the customer. In this program, admin (prudential employee) just need to know the amount of customer’s income that the program will then process the results of the estimated premi.The test results is concluded that the program estimates the premi can be used easily by the admin (prudential employee) and simplify admin decisions premi estimate to the customer.